BillQuick 2004. - Smith, Lee Anne (Architectural Record, 2004)
This article presents information on BillQuick 2004, from BQE Software Inc. It is a time-billing and project-management package designed for small- to medium-size professional service firms. It provides a library of invoice types that can be customized for billing and maintenance of project and financial records. Fees, hourly charges, and other budget information can be scheduled directly within BillQuick for specific projects, allowing billing statements to be tailored according to individual clientele rates and contracts. Users can synchronize between BillQuick record and QuickBooks banking information to reconcile financial statements.